Engineering Quantum Mechanics - Park, Seoung-Hwan. (Wiley-IEEE Press, 2011)
A clear introduction to quantum mechanics concepts Quantum mechanics has become an essential tool for modern engineering, particularly due to the recent developments in quantum computing as well as the rapid progress in optoelectronic devices. Engineering Quantum Mechanics explains the fundamentals of this exciting field, providing broad coverage of both traditional areas such as semiconductor and laser physics as well as relatively new yet fast-growing areas such as quantum computation and quantum information technology. The book begins with basic quantum mechanics, reviewing measurements and probability, Dirac formulation, the uncertainty principle, harmonic oscillator, angular momentum eigenstates, and perturbation theory. Then, quantum statistical mechanics is explored, from second quantization and density operators to coherent and squeezed states, coherent interactions between atoms and fields, and the Jaynes-Cummings model. From there, the book moves into elementary and modern applications, discussing such topics as Bloch theorem and effective mass theory, crystal orientation effects for zinc-blend and wurtzite Hamiltonian, and quantum entanglements and teleportation. There has been growing interest in the model of semiconductor lasers with non-Markovian relaxation. This book develops a non-Markovian model for the optical gain in semiconductor materials, taking into account the rigorous electronic band-structure and the non-Markovian relaxation using the quantum statistical reduced-density operator formalism. Many-body effects are taken into account within the time-dependent Hartree-Fock equations, and example programs based on Fortran 77 are provided for band-structures of zinc-blend quantum wells. Engineering Quantum Mechanics is intended for advanced undergraduate and graduate students in electrical engineering, physics, and materials science. It also provides the necessary theoretical background for researchers in optoelectronics or semiconductor devices.
Cover -- CONTENTS -- Preface -- PART I: Fundamentals -- 1: Basic Quantum Mechanics -- 1.1 MEASUREMENTS AND PROBABILITY -- 1.2 DIRAC FORMULATION -- 1.3 BRIEF DETOUR TO CLASSICAL MECHANICS -- 1.4 A ROAD TO QUANTUM MECHANICS -- 1.5 THE UNCERTAINTY PRINCIPLE -- 1.6 THE HARMONIC OSCILLATOR -- 1.7 ANGULAR MOMENTUM EIGENSTATES -- 1.8 QUANTIZATION OF ELECTROMAGNETIC FIELDS -- 1.9 PERTURBATION THEORY -- PROBLEMS -- REFERENCES -- 2: Basic Quantum Statistical Mechanics -- 2.1 ELEMENTARY STATISTICAL MECHANICS -- 2.2 SECOND QUANTIZATION -- 2.3 DENSITY OPERATORS -- 2.4 THE COHERENT STATE -- 2.5 THE SQUEEZED STATE -- 2.6 COHERENT INTERACTIONS BETWEEN ATOMS AND FIELDS -- 2.7 THE JAYNES8211;CUMMINGS MODEL -- PROBLEMS -- REFERENCES -- 3: Elementary Theory of Electronic Band Structure in Semiconductors -- 3.1 BLOCH THEOREM AND EFFECTIVE MASS THEORY -- 3.2 THE LUTTINGER8211;KOHN HAMILTONIAN -- 3.3 THE ZINC BLENDE HAMILTONIAN -- 3.4 THE WURTZITE HAMILTONIAN -- 3.5 BAND STRUCTURE OF ZINC BLENDE AND WURTZITE SEMICONDUCTORS -- 3.6 CRYSTAL ORIENTATION EFFECTS ON A ZINC BLENDE HAMILTONIAN -- 3.7 CRYSTAL ORIENTATION EFFECTS ON A WURTZITE HAMILTONIAN -- PROBLEMS -- REFERENCES -- PART II: Modern Applications -- 4: Quantum Information Science -- 4.1 QUANTUM BITS AND TENSOR PRODUCTS -- 4.2 QUANTUM ENTANGLEMENT -- 4.3 QUANTUM TELEPORTATION -- 4.4 EVOLUTION OF THE QUANTUM STATE: QUANTUM INFORMATION PROCESSING -- 4.5 A MEASURE OF INFORMATION -- 4.6 QUANTUM BLACK HOLES -- APPENDIX A: DERIVATION OF EQUATION (4.82) -- APPENDIX B: DERIVATION OF EQUATIONS (4.93) AND (4.106) -- PROBLEMS -- REFERENCES -- 5: Modern Semiconductor Laser Theory -- 5.1 DENSITY OPERATOR DESCRIPTION OF OPTICAL INTERACTIONS -- 5.2 THE TIME-CONVOLUTIONLESS EQUATION -- 5.3 THE THEORY OF NON-MARKOVIAN OPTICAL GAIN IN SEMICONDUCTOR LASERS -- 5.4 OPTICAL GAIN OF A QUANTUM WELL LASER WITH NON-MARKOVIAN RELAXATION AND MANY-BODY EFFECTS -- 5.5 NUMERICAL METHODS FOR VALENCE BAND STRUCTURE IN NANOSTRUCTURES -- 5.6 ZINC BLENDE BULK AND QUANTUM WELL STRUCTURES -- 5.7 WURTZITE BULK AND QUANTUM WELL STRUCTURES -- 5.8 QUANTUM WIRES AND QUANTUM DOTS -- PROBLEMS -- REFERENCES -- INDEX.
Keywords: Quantum theory; Stochastic processes; Engineering mathematics; Semiconductors -- Electric properties -- Mathematical models; Quantum theory; Stochastic processes; Engineering mathematics; Semiconductors -- Electric properties -- Mathematical models; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Quantum theory; Stochastic processes; Engineering mathematics; Semiconductors / Electric properties / Mathematical models; Electronic resource